Two new species of Ologamasus (Acari: Mesostigmata: Ologamasidae) from Brazil with a key to the world species of the genus - Santos, Jandir C. [UNESP]; Castilho, Raphael C. [UNESP]; Silva, Edmilson S.; De Moraes, Gilberto J. (Magnolia Press, 2015)
Ologamasus lucasi n. sp. and Ologamasus delaliberai n. sp. are described from adults collected from litter and soil in the State of Alagoas, northeastern of Brazil. A key for the separation of females of the 20 recognisable world species of Ologamasus is provided.